Immediate and long‐term effects of the COVID‐19 pandemic and lockdown on physical activity in patients with implanted cardiac devices. Issue 1 (10th December 2021) - Rosman, Lindsey; Mazzella, Anthony J; Gehi, Anil; Liu, Yutong; Li, Quefeng; Salmoirago‐Blotcher, Elena; Lampert, Rachel; Burg, Matthew M.
Abstract: Background: Physical activity (PA) is an important determinant of cardiovascular health that may be affected the COVID‐19 pandemic. Therefore, we examined the immediate and long‐term effects of the pandemic and lockdown on PA in patients with established cardiovascular risk. Methods: Objectively‐measured daily PA data was obtained from cardiovascular implantable electronic devices (CIEDs) from 3453 U.S patients (mean and standard deviations [SD] age, 72.65 [13.24] years; 42% women). Adjusted mixed‐effects models stratified by device type were used to compare daily PA from periods in 2020: pre‐lockdown (March 1–14), lockdown (March 15 to May 8), and the reopening phase of the pandemic (May 9 to December 31) versus 2019. Patient characteristics and events associated with inactivity during lockdown and the proportion of patients who returned to their 2019 PA‐level by the end of reopening phase (December 31, 2020) were examined. Results: Daily PA was significantly lower during the lockdown compared to the same period in 2019 (−15%; p  < .0001), especially for pacemaker patients, adults aged <65, and patients more active prior to lockdown. Non‐COVID hospitalization and ICD shock were similarly associated with low PA during lockdown ( p  = .0001). In the reopening phase of the pandemic, PA remained 14.4% lower in the overall sample and only 23% of patients returned to their 2019 PA level by the end of follow‐up. Conclusions: In this large cohort of patients with CIEDs, PA was markedly lower during the lockdown and remained lower for months after restrictions were lifted. Strategies to maintain PA during a national emergency are urgently needed.